Ambidextrous Lecturer: The Dualism Phenomena of Lecturer Role as a Scientist and an Academic Entrepreneur in Indonesian Universities - Nurul Safitri; Martani Huseini; Retno Kusumastuti (Technium Social Sciences Journal, 2023)
This study is to investigate the academic entrepreneurship in Indonesia from an ambidexterity perspective. The aim of this research is to analyze the academic entrepreneurship in Indonesia from an ambidexterity perspective. This study utilized the theory of ambidexterity by Birkinshaw and Gibson, particularly contextual ambidexterity and employed a quantitative methodology with surveyed 155 lecturers from Public Universities in Indonesia using online questionnaire. Employing SPSS as a data processing method, the results show a significant number of lecturers who desire to become academic entrepreneurs, but a smaller percentage of lecturers who actively seek more information about academic entrepreneurs. This result indicate the gap between intention to become academic entrepreneur and the behavior as academic entrepreneur. Tests of statistical result also indicate that personal networking and the personal capabilities of lecturers have a significant impact on academic entrepreneurship. However, partial testing shows the affect of personal networking is not significant.